Optimizing ADAS-Cog Worksheets: A Survey of Clinical Trial Rater s' Perceptions - M. Meyer, Stephen; A. Bertzos, Kristina; Perez, Magdalena; J. Connor, Donald; Schafer, Kimberly; Walter, Sarah (Current Alzheimer Research, 2017)
Background: The Alzheimer's Disease Assessment Scale-Cognitive subscale (ADASCog) remains the most widely used test of longitudinal cognitive functioning in Alzheimer's disease (AD) clinical trials. Unlike most neuropsychological tests, the ADAS-Cog source documentation worksheets are not uniform across clinical trials, and vary by document layout, inclusion of administration and/or scoring instructions, and documentation of subtest scoring (e.g., recording correct versus incorrect scores), among other differences. Many ADAS-Cog test administrators (raters) participate in multiple AD trials and switching between different ADAS-Cog worksheets may increase the likelihood of administration and/or scoring mistakes that lessen the reliability of the instrument. An anonymous online survey sought raters' experiences with ADAS-Cog worksheets and their opinions on the design and content of the worksheets. Results: Results of the survey indicated preference for structure and standardization of the ADASCog worksheets, which has been considered in the development of a standard ADAS-Cog source document by the Alzheimer's Disease Cooperative Study (ADCS) Working Group.
Keywords: Alzheimer' s disease